STUDI POTENSI PULAU PISANG BAGIAN UTARA UNTUK PERENCANAAN KAWASAN WISATA PANTAI, KABUPATEN LAMPUNG BARAT, PROVINSI LAMPUNG - Sitompul, Putra Charisma Chryssa; Subardjo, Petrus; Pratikto, Ibnu (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Faithful Cape Coast is one of Lampung destinations featured attraction and a tourist attraction in West Lampung regency which has considerable potential as a marine tourism area. This study aims to identify and assess physical potential of Pisang Island as coastal tourism area. The research was conducted in July-August 2011, this is because the month is a transitional season, when the season started, many people were coming to Pisang Island. The method used in this study is descriptive exploratory method. The analysis used in this study is the analysis of the suitability of tourism, namely by comparing the characteristics and quality of land to the land use requirements for specific tourism activities. The results of the study showed that the physical condition of the waters of North Pisang Island potential as marine tourism area, with some activity that is Coastal walk, Sun Bathing, and fishing. Based on the IKW for Coastal Walk into the category of class S1 (highly suitable) with IKW value by 93%, whereas for Sun Bathing in the category S1 (highly suitable) with IKW value by 94% and for Fishing in category S2 (Quite suitable) with IKW value by 70%.